Institutions and Investment in the South and East Asia and Pacific Region: Evidence from Meta-Analysis - Sridevi Yerrabati; Denise Donna Hawkes (Economics: The Open-Access, Open-Assessment E-Journal, 2016)
The ability of any country to attract inward FDI is considered to depend on the quality of the economic governance found within that state. This study seeks to explore the value of quality economic governance in attracting FDI in South and East Asia by meta-synthesising 771 estimates from 48 empirical studies published between 1980 and 2012. The authors find evidence that countries with good quality regulation and low levels of corruption are able to attract more FDI. They also find that countries with stronger legal systems are rewarded with higher levels of inward FDI. The results of the meta-regression suggest that investing in quality economic governance is rewarded in the global economy through high levels of inward FDI.
Keywords: F2; F3; F4; 330; FDI; governance; meta-regression analysis; systematic literature review; South and East Asia and Pacific countries